Mania Risk is Associated with Dominance Behavior in an Interpersonal Negotiation Task. Issue 4 (December 2014) - Fulford, Daniel; Sinclair, Sungchoon; John, Oliver P.; Johnson, Sheri L.
Researchers have noted strong parallels in the symptoms of mania—including grandiosity, hostility, goal-driven behavior, and overly sexualized behavior—and dominance. Drawing on these parallels, it has been hypothesized that bipolar disorder might be related to dysregulations of the dominance system, which includes dominance motivation, power, and dominance behavior. The goal of the current study was to consider whether manic tendencies related to the dominance system as measured in an ecologically valid experimental paradigm. Participants took part in small group interactions in which they negotiated merit pay for candidates seeking promotion. They completed ratings of their own and peers' dominance behaviors during the interaction. All participants also completed the Hypomanic Personality Scale to assess risk for mania, as well as scales to assess for current (hypo)mania and history of depression. Whereas history of depression was related to lower dominance motivation, mania risk was related to dominance behavior during the task, and peers rated this dominance behavior unfavorably. Findings provide a framework for understanding some of the social problems observed in bipolar disorder, with both depression history and mania risk contributing to dysregulations in the dominance system.